Practice of contraception in this modern world: still a myth? - Bansiwal, Reeta; Singh, Pushpa; Bajpai, Shruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective: To assess the attitude, knowledge and practice of contraception among MTP seekers women attending Family Planning OPD. Methods: 150 women attending family planning clinic and requesting for Medical Termination of Pregnancy (MTP), were interrogated on a pre- structured questionnaire and their knowledge, attitude and practice about contraception were assessed. Results: Of the women 80% women had some or the other knowledge of contraception but still 92 (61.3%) were not using any contraception 92 (61.3%), 54 (36%) were using barrier method and only 4 (2.6%) were used OCP’s. The request for MTP was mainly on grounds of unplanned pregnancy and completed family in 57.3% cases followed by previous child small 42 (28%). Of the women, only 38 (25.3%) had heard about emergency contraceptives and only few had used them off and on. The various methods of contraception accepted by the women post abortion were IUDs by 91 (61.3%) and female sterilization by 55 (36.6%). Statistical analysis was done using SPSS software 15. Conclusions: Practice of contraception is still a myth. There is a great need to strengthen the awareness among people by various programmes and the target group should be both males and females.